Should They Stay or Should They Go? Attitudes Towards Immigration in Europe. (1st July 2014) - Bridges, Sarah; Mateut, Simona
Abstract This paper examines the main determinants of individual attitudes towards immigration in Europe. Our results suggest that both economic and non‐economic variables shape attitudes towards immigration, but the relative importance of these factors depends crucially on the race/ethnicity of the arriving immigrants. While fears over labour market competition are more likely to shape attitudes towards the arrival of same race immigrants, more exposure to immigrants reduces opposition towards the arrival of different race immigrants. These findings persist after controlling for socioeconomic characteristics, and after exploiting the data to allow for cohort‐specific effects.